1987
DOI: 10.1149/1.2100727
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐Transfer Studies in a Plating Cell with a Reciprocating Paddle

Abstract: Deposition of Cu2+ ions under mass‐transfer limited conditions was used to study mass transfer in an electrochemical cell with a reciprocating paddle. The reciprocating paddle induced a nearly periodic mass‐transfer limited current. Fourier analysis of the current revealed that the frequency of maximum power dissipation was not necessarily at the paddle frequency but depended upon the test cathode position in the cell. The time‐averaged Sherwood number for the Cu2+ ions was found to depend on the paddle Reynol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…1). Experimental data (Schwartz et al, 1987;Rice et al, 1988) and numerical simulations Mandin et al, 2007) show that geometrical parameters of the paddle, size and aspect ratio of the cell and paddle shape have a strong influence on mass-transfer phenomena within the electrochemical cell. In literature a relationship has been proposed between the diffusion layer thickness and paddle geometrical parameters.…”
Section: Paddle-cell Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Experimental data (Schwartz et al, 1987;Rice et al, 1988) and numerical simulations Mandin et al, 2007) show that geometrical parameters of the paddle, size and aspect ratio of the cell and paddle shape have a strong influence on mass-transfer phenomena within the electrochemical cell. In literature a relationship has been proposed between the diffusion layer thickness and paddle geometrical parameters.…”
Section: Paddle-cell Systemmentioning
confidence: 99%
“…Results from studies on the paddle-cell (Schwartz et al, 1987;Rice et al, 1988; suggest that the most important parameters should be the distance between the comb and the cathode (g, see figure 2), the stirring frequency ( f ) and stroke (S, maximum amplitude of stirring), the width of the comb (h), the shape of the teeth section, and the dimensions of the cell (L and H). Prior unpublished studies also showed that the mesh of the comb (M) could have an influence on the hydrodynamical conditions.…”
Section: Electrochemical Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…The design attributed to Romankiw includes a pair of opposing rectangular prisms that moves back and forth over a horizontal working electrode wafer at a constant oscillating frequency, parallel to a counterelectrode; and was a significant innovation to achieve uniform current distribution along the wafer, providing a more meaningful alternative to the fountain cell. The modeling of the transport boundary layer thickness, 11 established by the periodic wake trailing the paddle as it passes over the cathode, helped to create a significant design tool in widespread use today.…”
Section: Heavy Metal Ed In Porous Electrodesmentioning
confidence: 99%
“…Mass transport conditions are fairly uniform although the mass transport rate may vary periodically with time as the paddle moves back and forth. 84 Through hole plating poses difficult current distribution problems because the metal must be deposited uniformly into a high aspect ratio geometry. The current distribution in through hole plating using direct current 85,86 and pulse current 87,88 has been studied extensively.…”
Section: Electrochemical Engineering Aspects Of Electrodepositionmentioning
confidence: 99%